Theoretical study of the open-flavored tetraquark $$T_{c\bar{s}}(2900)$$ T c s ¯ ( 2900 ) in the process $$\bar{B}_s^0 → K^0 D^0 π ^0$$ B ¯ s 0 → K 0 D 0 π 0 - Wen-Tao Lyu; Man-Yu Duan; Xiaoyu Wang; Dian-Yong Chen; En Wang (European Physical Journal C: Particles and Fields)
Abstract Recently, the LHCb Collaboration has measured two decay processes $$B^0→ \bar{D}^0D_s^+π ^-$$ B 0 → D ¯ 0 D s + π - and $$B^+→ D^-D_s^+π ^+$$ B + → D - D s + π + related to isospin symmetry, where two new open-flavored tetraquark states $$T_{c\bar{s}}(2900)^0$$ T c s ¯ ( 2900 ) 0 and $$T_{c\bar{s}}(2900)^{++}$$ T c s ¯ ( 2900 ) + + that belong to an isospin triplet were observed in the $$D_s^+π ^-$$ D s + π - and $$D_s^+π ^+$$ D s + π + invariant mass distributions. In this work, we have investigated the validity of the process $$\bar{B}_s^0→ K^0D^0π ^0$$ B ¯ s 0 → K 0 D 0 π 0 as the promising process to confirm the existence of $$T_{c\bar{s}}(2900)^0$$ T c s ¯ ( 2900 ) 0 resonance. Taking into account the tetraquark state $$T_{c\bar{s}}(2900)$$ T c s ¯ ( 2900 ) , as well as intermediate resonances $$K^*(892)$$ K ∗ ( 892 ) , $$K_0^*(1430)$$ K 0 ∗ ( 1430 ) , and $$K_2^*(1430)$$ K 2 ∗ ( 1430 ) , it has been shown that a clear peak of the open-flavored tetraquark $$T_{c\bar{s}}(2900)$$ T c s ¯ ( 2900 ) appears in the $$K^0D^0$$ K 0 D 0 invariant mass distribution of the process $$\bar{B}_s^0→ K^0D^0π ^0$$ B ¯ s 0 → K 0 D 0 π 0 , which could be tested by future experiments.